Novel Insight into Culicoides (Diptera: Ceratopogonidae) Host Preferences and the First Evidence of Avian Haemosporidian Parasites in Biting Midges in Slovakia - Janošková, Nikola; Schreiberová, Andrea; Korytár, Ľuboš; Minichová, Lenka; Kočišová, Alica (Pathogens (Basel, Switzerland), 2025)
Culicoides biting midges (Diptera: Ceratopogonidae) are important vectors of avian haemosporidian parasites. Understanding their host preferences is crucial for elucidating transmission routes of vector-borne pathogens. In Slovakia, such knowledge is limited, particularly in forested wetlands. This study aimed to identify Culicoides species, their host preferences, and haemosporidian parasites in a wetland ecosystem at the Bird Ringing Station in Drienovec. Midges were collected in 2022 using UV light traps at two sites. In total, 2344 Culicoides individuals of 19 species were collected. Host blood was identified and DNA subsequently extracted from 36 engorged females, revealing feeding on three mammal and five bird species. The most frequently identified host was roe deer (Capreolus capreolus), predominantly fed upon by Culicoides obsoletus (Meigen 1818). Notably, avian haemosporidian DNA was detected for the first time in Slovakia in three Culicoides females. In two Culicoides alazanicus Dzhafarov 1961 individuals, DNA of Haemoproteus asymmetricus (TUPHI01) and Plasmodium matutinum (LINN1) was confirmed, both associated with avian blood from Turdus sp. One Culicoides festivipennis Kieffer 1914 female carried Haemoproteus tartakovskyi (HAWF1) and fed on Coccothraustes coccothraustes. These findings highlight the potential role of local Culicoides species in transmitting avian pathogens and underscore the importance of monitoring their ecology.
Keywords: Slovakia; mokřady; Slovenská republika; molecular detection; Haemosporida; Wetlands; hmyz - vektory; biting midges; hostitelská specificita; ptáci; Birds; Animals; ženské pohlaví; zvířata; host blood; Ceratopogonidae; Insect Vectors; Female; Host Specificity; potential vectors